2021
DOI: 10.1186/s12889-021-10725-9
|View full text |Cite
|
Sign up to set email alerts
|

Homebound by COVID19: the benefits and consequences of non-pharmaceutical intervention strategies

Abstract: Background Recent research has been conducted by various countries and regions on the impact of non-pharmaceutical interventions (NPIs) on reducing the spread of COVID19. This study evaluates the tradeoffs between potential benefits (e.g., reduction in infection spread and deaths) of NPIs for COVID19 and being homebound (i.e., refraining from interactions outside of the household). Methods An agent-based simulation model, which captures the natural… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…The NPIs implemented in New York City were estimated to have reduced cases numbers by 72% and deaths by 76% [67]. While some studies shows the relationship between single NPI and the reduction in COVID-19 incidences or reproduction number, others try to identify the more effective blends of NPI sub-categories [68][69][70]. However, researchers also find the synergistic benefits of implementing a suite of multiple NPIs, which lends support to our approach of assessing the relationship between overall NPIs and deaths [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…The NPIs implemented in New York City were estimated to have reduced cases numbers by 72% and deaths by 76% [67]. While some studies shows the relationship between single NPI and the reduction in COVID-19 incidences or reproduction number, others try to identify the more effective blends of NPI sub-categories [68][69][70]. However, researchers also find the synergistic benefits of implementing a suite of multiple NPIs, which lends support to our approach of assessing the relationship between overall NPIs and deaths [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of other non-pharmaceutical public health measures, including workplace closings, voluntary quarantine compliance, shelter-in-place, and masking mandates have been considered and compared in prior work [ 7 , 9 , 20 , 31 , 53 – 56 ]. Some studies found that the public health effects of school closures are similar to that of workplace closures [ 20 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…PIPs are all the actions of individuals that aim to control the pandemic spread. Indeed, policy makers use multiple types of PIPS, such as lockdowns [81] and artificial job separations [25]. For airborne pandemics, mask-wearing PIP is considered efficient and was used for the COVID-19 pandemic [82] and the influenza pandemic [83] to name a few.…”
Section: Pandemic Intervention Policiesmentioning
confidence: 99%
“…For airborne pandemics, mask-wearing PIP is considered efficient and was used for the COVID-19 pandemic [82] and the influenza pandemic [83] to name a few. However, in practice, masks differ in their effectiveness and the portion of the population that wears them [81,82,84]. Hence, we define the mask-wearing PIP using two parameters η ∈ [0, 1] and κ ∈ [0, 1] that stand for the portion of the population that wears a mask and the portion of the pathogen particles filtered by the mask, respectively.…”
Section: Pandemic Intervention Policiesmentioning
confidence: 99%